Budoucnost metropolitní spolupráce v České republice: rozvoj, správa, řízení - Kunc, Josef (Masaryk University Press, 2023)
Title in English: The future of metropolitan cooperation in the czech republic: development, governance, management Metropolitan regions are engines of economic growth, where research, innovation, technology and creative human potential are concentrated. The cooperation of municipalities in metropolitan regions in economically developed Europe dates back to the mid-1990s, while in the Czech Republic this new form of cooperation has been discussed more intensively since 2014, when three metropolitan areas and ten urban agglomerations were defined. However, there is still no systemic coordination of the problems and needs of metropolitan areas. The first activities aimed at real strengthening of metropolitan cooperation and development took place in the Brno Metropolitan Area within the framework of the TAČR ÉTA project "Institutionalization of metropolitan cooperation as a factor to increase the motivation of municipalities to cooperate in metropolitan areas". The aim of the publication is to present the results of the project, experiences from abroad and their possible application in the Czech environment, as well as real steps to set up metropolitan inter-municipal cooperation.